Inorganic Waste Utilization Training for Teachers at MI Muhammadiyah Kedungbanteng: Pelatihan Pemanfaatan Sampah Anorganik bagi Guru MI Muhammadiyah Kedungbanteng - Fihayati, Zuyyina; Rezania, Vanda; Aulina, Choirun Nisak; Azizah, Dian Nur; Safitri, Silvia Gita (Procedia of Social Sciences and Humanities, 2022)
Everyone must produce garbage and gradually the garbage will accumulate. Therefore, it is necessary to provide clear information for people who have minimal education on waste management. This bias starts from the students. MI Muhammadiyah Kedungbanteng has several problems related to inorganic waste, including: (1) the lack of teacher skills in the use of inorganic waste in schools and (2) the unavailability of inorganic waste processing programs. This is what underlies the activities of the Institutional Community Partnership Program (PKaMI) implemented at the MI. The objectives of PKaMI activities include: (1) increasing the ability of teachers to utilize inorganic waste and (2) implementing inorganic waste management programs in schools. The results obtained from this program are that teachers begin to have knowledge of inorganic waste management and have an understanding of how to implement waste management programs in the school curriculum.